An Empirical Analysis of Inclusive Finance Support to the Development of Rural Revitalization in Linyi - ZHAO, JUAN (Pacific International Journal, 2022)
This research adopts the coefficient of variation method to construct Linyi inclusive financial development index and rural revitalization index. According to the standard of international inclusive financial development level, when the inclusive financial development index is between 0 and 1, it indicates that inclusive financial development in the region is from a low level to a high level. The research finds that the degree of inclusive financial development in Linyi is different. Apart from Lanshan District, the level of inclusive financial development in other districts and counties is low, with the unstable inclusive financial development index between 0.01 and 0.15 in most years. After measuring the rural revitalization index, it is found that the Linyi’s rural development is better and the regional development is more balanced. Through empirical analysis, the research comes to a conclusion that inclusive finance can effectively promote the rural revitalization in Linyi. Based on the above analysis, the paper puts forward the following suggestions: Linyi should optimize the layout of financial resources, improve the rural financial ecological environment, perfect the credit system of farmers, improve the quality of financial services, and increase the investment in agriculture, forestry and water to guide the upgrading of agricultural industry structure.